The quality of life of patients after liver transplantation - Tamer, Murat; Yava, Ayla (Annals of Medical Research, 2022)
Aim: With increased survival rates after liver transplantation (LT), studies have focused on improving the quality of life in these patients. The purpose of this study is to assess the quality of life levels of recipients after LT. Materials and Methods: This descriptive study was conducted with 103 voluntary patients between January 01-May 15, 2015. The sample of the study consisted of the patients who had liver transplantation and met the inclusion criteria. The data were collected using personal and disease information form and SF-36 health survey. Results: It was found in the study that the mean score of the Physical Component Summary (PCS) was 39.90±8.53 and the mean score of the Mental Component Summary (MCS) was 43.93±9.86. The patients who underwent LT had a moderate quality of life. The MCS score enhanced with increasing level of education. The PCS score is higher in those with men, single patients, cadavers as the source of transplantation, and those without a prolonging post-operative hospitalisation. Another finding of the study indicated that PCS score enhanced as the time elapsed after transplantation increased. In addition, patients with chronic diseases had lower physical health quality of life. Conclusion: Although many complications develop in most of the patients, LT can make the patient more functional in many areas of life compared to their pre-transplantation life. The patients should be referred to other departments regularly to keep chronic diseases under control.
Keywords: Liver transplantation; quality of life; SF-36; nursing